Lignocellulose-Based Materials and Their Application in the Removal of Dyes from Water: A Review - Sanchez-Poblete, J; Roa-Ruiz, K; Oyarce-Riveros, E; Alsamman-, M; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2021)
The search for new technologies and eco-sustainable materials for wastewater treatment has been increasing, and adsorption technology stands out because of its simple and low-cost process. This review discuss adsorbents based on lignocellulosic biomass (LB) because of their availability in nature, attractive chemical composition (lignin, cellulose and hemicellulose) and structural composition (various functional groups capable of capturing molecules of organic dyes in aqueous solution). LB allows for the elaboration of a diverse range of efficient, reusable, economical and environmentally friendly lignocellulosic materials (LM) that may present competitive dye adsorption abilities. In addition, this review also discuss the stabilization of metallic nanoparticles or metallic oxides in lignocellulosic matrices or their derivatives and their ability to degrade the organic dyes previously adsorbed in the material has attracted considerable scientific attention due to their simplicity, reusability, and high catalytic activity and because they do not generate byproducts that pollute the environment. © 2021 Elsevier B.V.